2002
DOI: 10.1152/ajpcell.00112.2002
|View full text |Cite
|
Sign up to set email alerts
|

Global/temporal gene expression in diaphragm and hindlimb muscles of dystrophin-deficient (mdx) mice

Abstract: The mdx mouse is a model for human Duchenne muscular dystrophy (DMD), an X-linked degenerative disease of skeletal muscle tissue characterized by the absence of the dystrophin protein. The mdx mice display a much milder phenotype than DMD patients. After the first week of life when all mdx muscles evolve like muscles of young DMD patients, mdx hindlimb muscles substantially compensate for the lack of dystrophin, whereas mdx diaphragm muscle becomes progressively affected by the disease. We used cDNA microarray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 54 publications
3
38
0
1
Order By: Relevance
“…Several transcriptome studies in Dmd mdx mouse were published in the last years, [12][13][14][15][16][17][18][19][20] but no studies in Large myd − / − nor in Dmd mdx /Large myd − / − were performed. 9 In Dmd mdx , similar data to the observed in our study were described by Boer et al 14 and Porter et al 17,21 Using an Affymetrix chip of about 12 000 genes/EST, Boer et al 14 identified 58 DEGs in Dmd mdx limb muscles, from which 49 were unregulated while only 9 were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Several transcriptome studies in Dmd mdx mouse were published in the last years, [12][13][14][15][16][17][18][19][20] but no studies in Large myd − / − nor in Dmd mdx /Large myd − / − were performed. 9 In Dmd mdx , similar data to the observed in our study were described by Boer et al 14 and Porter et al 17,21 Using an Affymetrix chip of about 12 000 genes/EST, Boer et al 14 identified 58 DEGs in Dmd mdx limb muscles, from which 49 were unregulated while only 9 were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Several microarray-based studies of gene expression in normal and diseased states have been performed on human skeletal muscles obtained at biopsy or autopsy (1,8,20,21,33) and on murine skeletal muscle obtained immediately postmortem (30,32,37,40). These studies identified a number of genes in various functional categories that are differentially expressed in the disease states, suggesting that major alterations in tissue have far-reaching consequences for gene expression.…”
mentioning
confidence: 99%
“…However, there were divergences between diaphragm and limb muscle within themes of which specific genes were altered, especially within the inflammatory and muscle-specific gene categories. Rouger et al (38) studied both diaphragm and limb muscle using cDNA microarrays that tested expression of a much more focused group of 1,082 genes. They found some genes with altered expression in both muscle groups, others with altered expression in diaphragm only or limb muscle only, and yet others with altered but different expression in the two muscle groups.…”
Section: Discussionmentioning
confidence: 99%